2014
DOI: 10.1371/journal.pone.0101843
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Filters to Sense: Great Variability of Antennal Morphology and Sensillar Equipment in Gall-Wasps (Hymenoptera: Cynipidae)

Abstract: Comparative studies on antennal sensillar equipment in insects are largely lacking, despite their potential to provide insights into both ecological and phylogenetic relationships. Here we present the first comparative study on antennal morphology and sensillar equipment in female Cynipoidea (Hymenoptera), a large and diverse group of wasps, with special reference to the so-called gall-wasps (Cynipidae). A SEM analysis was conducted on 51 species from all extant cynipoid families and all cynipid tribes, and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(62 citation statements)
references
References 87 publications
(195 reference statements)
8
53
1
Order By: Relevance
“…These wasps depend largely on species-specific chemicals to discriminate their host figs from other fig species (Hossaert-Mckey et al, 2010;Proffit et al, 2007;Wang et al, 2013). These types of antennal sensilla never occur simultaneously on a single species and their types are consistent with those observed on other hymenopteran parasitoids (Amornsak et al, 1998;Basibuyuk and Quicke, 1999;Ochieng et al, 2000;Onagbola and Fadamiro, 2008;Polidori and Nieves-Aldrey, 2014;Steinbrecht, 1997;van Baaren et al, 2007). The sensilla observed on C. emarginatus were similar to those found on the closely related fig pollinating wasp C. solmsi marchali (Li et al, 2009;Meng et al, 2016).…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…These wasps depend largely on species-specific chemicals to discriminate their host figs from other fig species (Hossaert-Mckey et al, 2010;Proffit et al, 2007;Wang et al, 2013). These types of antennal sensilla never occur simultaneously on a single species and their types are consistent with those observed on other hymenopteran parasitoids (Amornsak et al, 1998;Basibuyuk and Quicke, 1999;Ochieng et al, 2000;Onagbola and Fadamiro, 2008;Polidori and Nieves-Aldrey, 2014;Steinbrecht, 1997;van Baaren et al, 2007). The sensilla observed on C. emarginatus were similar to those found on the closely related fig pollinating wasp C. solmsi marchali (Li et al, 2009;Meng et al, 2016).…”
Section: Discussionmentioning
confidence: 58%
“…Hair-like TS were abundant on the antennae of the four study species and have been reported on the antennae of nearly all investigated hymenopteran parasitoids (Amornsak et al, 1998;Bleeker et al, 2004;Das et al, 2011;Gao et al, 2007;Li et al, 2009Li et al, , 2014Meng et al, 2016;Ochieng et al, 2000;Onagbola and Fadamiro, 2008;Polidori and Nieves-Aldrey, 2014;Romani et al, 2010;Roux et al, 2005;van Baaren et al, 2007). In the four analysed species, the TS occur in various forms and lengths and at different locations, but they always present more longitudinal grooves on the ventral side in the direction of the antennal axis.…”
Section: Putative Functions Of the Different Sensilla Typesmentioning
confidence: 74%
See 2 more Smart Citations
“…The perception of such stimuli, which can often be released in very small amounts or be biologically active for a short time, has driven the antennal sensory structures of female parasitoids toward high specialization, leading to the evolution of specific sensilla (Barlin and Vinson, ; Bin et al, ; Isidoro et al, ; Basibuyuk and Quicke, ; van Baaren et al, ; Klopfstein et al, ; Romani et al, ; Ruschioni et al, ; Polidori and Nieves‐Aldrey, ).…”
Section: Introductionmentioning
confidence: 99%